Physical Therapy for Young Children Diagnosed with Autism Spectrum Disorders–Clinical Frameworks Model in an Israeli Setting - Atun-Einy, Osnat; Lotan, Meir; Harel, Yael; Shavit, Efrat; Burstein, Shimshon; Kempner, Gali (Frontiers in Pediatrics, 2013)
Recent research findings suggest that many children with Autism Spectrum Disorders (ASD) demonstrate delayed and atypical motor achievements. It has now become clear that a more holistic, integrative and multi-disciplinary intervention is required to effectively address the motor-related impairments of this population. It is also crucial to ensure that this group of clients has access to early physical therapy (PT) interventions. Despite accumulating research on physical interventions, little is known about intervention model for implementation at a national level. This report introduces a model that uniquely illustrates implementation of PT services for a large number of children with ASD. The model has been operating for the past two years in one country (Israel), and includes an optional implementation model of PT practice settings for young children diagnosed with ASD. The Israeli setting offers a unique opportunity for implementing PT services for a multitude of children with ASD on a regular basis as an accepted/needed service. The initial outcomes of the present implementation suggest that an intensive PT intervention program might enhance therapeutic outcomes for this population, and contribute to our knowledge on the